Multi-Step Estimation for Forecasting. - Clements, M; Hendry, D (Department of Economics (University of Warwick), 1996)
We delineate conditions which favour multi-step, or dynamic estimation for multi-step forecasting. An analytical example shows how dynamic estimation (DE) may accomodateincorrectly-specified models as the forecast lead alters, improving forecast performance for some mis-specifications. However, in correctly-specified models, reducing finite-sample biases does not justify DR. In a Monte Carlo forecasting study for integrated processes, estimating a unit root in the presence of a neglected negative moving-average error may favour DR, though other solutions exist to that scenario. A second Monte Carlo study obtains the estimator biases and explains these using asymptotic approximations.